1995
DOI: 10.1007/bf00183624
|View full text |Cite
|
Sign up to set email alerts
|

Technique and results of interstitial laser coagulation

Abstract: By use of thermal "ablation" techniques to apply heat to the prostate from the urethra, the coagulation volume is limited by the limited penetration depth of suitable radiation sources, e.g., lasers, and by heat conduction. Secondarily, the coagulated tissue is removed by sloughing. Interstitial heat application was expected to overcome these problems. Our initial in vitro and animal studies using different light guides for interstitial Nd:YAG laser radiation showed that small, carbonized lesions were created … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 32 publications
3
42
1
2
Order By: Relevance
“…The results for symptom reduction are comparable with those reported by others [4,8,10,17,22]. In a large study by Emberton et al [2] of > 3000 patients treated by TURP the AUA score decreased from a mean of 20.1 at baseline to 7.4 at 3 months.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results for symptom reduction are comparable with those reported by others [4,8,10,17,22]. In a large study by Emberton et al [2] of > 3000 patients treated by TURP the AUA score decreased from a mean of 20.1 at baseline to 7.4 at 3 months.…”
Section: Discussionsupporting
confidence: 87%
“…ILC has documented efficacy and an acceptable frequency of side-effects [4][5][6][7]. In some aspects ILC seems to offer an advantage over TURP; blood loss is minimal and the risk of TUR syndrome is eliminated, as saline rather than glycine is used as the irrigant.…”
Section: Introductionmentioning
confidence: 99%
“…Muschter et al ., who first introduced this approach, reported significant improvement in clinical and voiding parameters with minimum morbidity. 1,2 We have previously reported that satisfactory results were obtained with ILC and that an improvement of symptoms lasted through 12 months. [3][4][5] To date, no long-term follow-up results after the ILC procedure have been reported.…”
Section: Introductionmentioning
confidence: 96%
“…The singular noncontact application technique described by Kabalin [12]was followed by contact irradiation of all surfaces of the prostatic urethra. ILCP was carried out as described by Muschter and Hofstetter [13]by introducing the ITT (Dornier ITT – light quide interstitial thermotherapy) fiber into chosen sites of prostatic lobes and irradiating them using a lower power (from 20 to 7.5 W) for 5 min. The duration of the two laser–therapy methods was similar and varied from 20 to 70 min depending on the size of the prostate, i.e.…”
Section: Methodsmentioning
confidence: 99%